In vitro effects of novel type M-V-O derivatives on Xanthine Oxidase - Kaya, Mustafa Oğuzhan; Gül, Gülşah í‡eliÌ‡k; Kurtuluş, Figen (Cellular and Molecular Biology, 2017)
Xanthine Oxidase (XO) is related with different diseases such as vascular, gout, nephropathy and renal stone diseases that are relevant to high uric acid levels and oxidative stress. Some common natural inhibitors of xanthine oxidase are known as rosmarinic acid and apigenin. With this study, we aimed to determine inhibitory effects of originally synthesized new generation transition metal vanadates on Xanthine Oxidase (XO) from bovine milk. Because, Xanthine oxidase inhibitors are typically used in the treatment of gout and nephropathy and renal stone diseases linked to hyperuricaemia. We found considerable IC50 constants for inhibition of XO. Among the synthesized compounds, Cu"’V"’O was found to be the most active (IC50 = 7.119 mM) for inhibition of XO.